Recent Advances in the Use of Focused Ultrasound as a Treatment for Epilepsy - Lescrauwaet, Emma; Vonck, Kristl; Sprengers, Mathieu; Raedt, Robrecht; Klooster, Debby; Carrette, Evelien; Boon, Paul (Frontiers in Neuroscience, 2022)
Epilepsy affects about 1% of the population. Approximately one third of the patients with epilepsy are drug-resistant (DRE). Resective surgery is an effective treatment for DRE, yet invasive, and not all DRE patients are suitable resective surgery candidates. Focused ultrasound, a novel non-invasive neurointerventional method is currently under investigation as a treatment alternative for DRE. By emitting one or more ultrasound waves, FUS can target structures in the brain at millimeter resolution. High intensity focused ultrasound (HIFU) leads to ablation of tissue and could therefore serve as a non-invasive alternative for resective surgery. It is currently under investigation in clinical trials following the approval of HIFU for essential tremor and Parkinson’s disease. Low intensity focused ultrasound (LIFU) can modulate neuronal activity and could be used to lower cortical neuronal hyper-excitability in epilepsy patients in a non-invasive manner. The seizure-suppressive effect of LIFU has been studied in several preclinical trials, showing promising results. Further investigations are required to demonstrate translation of preclinical results to human subjects.